Aerial root rights in aesthetic heterotopias - Cruz Méndez, Itandehui Nahielly (Re-visiones, 2025)
This text addresses processes of collaborative imagination in autonomous normative systems, which, through aesthetic practices, have created aerial root rights to imagine and organize heterotopic spaces of life. I present the case of the performance practices carried out in the Zapotec community of Santiago Xanica, in Oaxaca. This practices fostered a reconfiguration of the sensible and activated a political imagination that made local historical problems visible and reorganized the intersubjective relationships that led the participants of the Sembrando Teatro group to peacefully take over Finca Alemania to create an autonomous educational center.
Keywords: aerial root rights; aesthetics heteropia; CODEDI Training Center; communal aesthetics; Santiago Xanica